Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21608/zjar.2019.40946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilization and Some Stimulants on Dry Weight, Yield, Bulb Quality and Storability of Garlic

Abstract: Two filed experiments were carried out during the winter seasons of 2016/2017 and 2017/2018 at the Experimental Farm, El-Gemmeiza, Agric Res. Station, (ARC), Gharbya Governorate (Middle Delta, Egypt), to study the effect of nitrogen fertilization at 90 and 120 kg/fad., and some stimulants; viz, salicylic acid (SA at 100 mg/l ), lithovit at 2 g/l and algae extract at 2%, beside unsprayed treatment on dry weight, yield, bulb quality and storability of garlic, Balady cultivar under clay soil conditions using floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies with different onion cultivars during storage indicate that lower mass losses are correlated with higher dry matter accumulation in the bulbs (Kahsay et al 2013), as observed in this study (Table 2) with 'B' treated with SC and FS and 'P' treated with FA, SC and FS showed an increase in dry mass, which resulted in less bulb loss in storage (Table 3). In addition, the application of humic substances and microalgae extract in plants, provided the bulbs in storage lower mass losses in relation to the control, hence, this result was justified by the greater accumulation of dry matter and total soluble solids (Shehata et al 2017;Mansour et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with different onion cultivars during storage indicate that lower mass losses are correlated with higher dry matter accumulation in the bulbs (Kahsay et al 2013), as observed in this study (Table 2) with 'B' treated with SC and FS and 'P' treated with FA, SC and FS showed an increase in dry mass, which resulted in less bulb loss in storage (Table 3). In addition, the application of humic substances and microalgae extract in plants, provided the bulbs in storage lower mass losses in relation to the control, hence, this result was justified by the greater accumulation of dry matter and total soluble solids (Shehata et al 2017;Mansour et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the other levels in both seasons respectively. The stimulating effect of organic manure in increasing essential oil yield was reported by Gahory et al (2022) on coriander plants, Ali et al (2017) on fennel plants, Al-Fraihat et al (2023b) on rosemary Rosmarinus officinalis L. plants, Abdullah et al (2012), on rosemary Rosmarinus officinalis L. plants, Mansour et al (2002) on spearmint and marjoram plants, Al-Fraihat et al (2011) on marjoram plants, El-Gendy et al (2001) on Sweet basil plants and Gharibe et al (2008) on Marjoram (Majorana hortensis) Plant, Darwish et al (2011) on Salvia officinalis plants.…”
Section: Volatile Oil Productionmentioning
confidence: 95%